Daytime sleepiness and BMI exhibit gender and age differences in patients with central disorders of hypersomnolence - Ferrazzini, Laura; Schmidt, Markus; Zhang, Zhongxing; Khatami, Ramin; Dauvilliers, Yves; Barateau, Lucie; Mayer, Geert; Pizza, Fabio; Plazzi, Giuseppe; Gool, Jari K; Fronczek, Rolf; Lammers, Gert Jan; et al. (Journal of sleep research, 2025)
The aim of the present study was to examine gender and age-specific effects on subjective daytime sleepiness (as measured by the Epworth Sleepiness Scale), body weight and eating behaviour in patients with central disorders of hypersomnolence. Based on the European Narcolepsy Network database, we compared 1035 patients with narcolepsy type I and 505 patients with other central disorders of hypersomnolence ("narcoleptic borderland"), including narcolepsy type II (N = 308) and idiopathic hypersomnia (N = 174), using logistic regression and general linear models. In the entire study population, the Epworth Sleepiness Scale was higher in women (N = 735, mean age = 30 years, mean Epworth Sleepiness Scale = 16.6 ± SD 3.9) than in men (N = 805, mean age = 32 years, mean Epworth Sleepiness Scale = 15.8 ± SD 4.4). In women with narcolepsy type I (N = 475), both Epworth Sleepiness Scale and body mass index increased in parallel with age. In women of the narcoleptic borderland (N = 260), the Epworth Sleepiness Scale markedly peaked in their early 30s, while body mass index only started to rise at that age. This rise in body mass index following the Epworth Sleepiness Scale peak cannot be explained by sleepiness-induced uncontrolled eating, as self-reported uncontrolled eating was negatively associated with the Epworth Sleepiness Scale in this group. We propose that the narcoleptic borderland harbours a unique cluster of women in their fertile years with an unexplored aetiology requiring further investigation towards tailored interventions.
Keywords: Young Adult; stravovací zvyklosti; Disorders of Excessive Somnolence; Male; obesity; mladý dospělý; Adolescent; sexuální faktory; impulsive eating behaviour; excessive daytime sleepiness; Adult; Age Factors; dospělí; mužské pohlaví; Narcolepsy; sex; Body Weight; mladiství; hypersomnia; lidé; ženské pohlaví; poruchy nadměrné spavosti; Humans; Body Mass Index; Sex Factors; narkolepsie; věkové faktory; index tělesné hmotnosti; Female; lidé středního věku; tělesná hmotnost; Middle Aged; Feeding Behavior